NMR‐based evaluation of the metabolic profile and response to dichloroacetate of human prostate cancer cells. (17th March 2014) - Kailavasan, Mithun; Rehman, Ishtiaq; Reynolds, Steven; Bucur, Adriana; Tozer, Gillian; Paley, Martyn
<x xml:space="preserve">Abstract</x> The aim of this study was to evaluate the metabolic profile of human prostate cancer cells that have different metastatic potential and to determine their response to dichloroacetate (DCA) using NMR technology. Two isogenic human prostate cancer cell lines, differing in their metastatic potential [LNCaP (poorly metastatic) and LNCaP‐LN3 (highly metastatic)], were studied. Metabolite ratios from NMR spectral integrals acquired at a field strength of 9.4 T using a 5‐mm broadband probe with an NMR‐compatible bioreactor were compared in the presence and absence of the pyruvate dehydrogenase kinase inhibitor DCA. Lactate dehydrogenase (LDH) isoenzymes were assessed by zymography. Following the treatment of cells with 50 mm DCA, there was a significant reduction in the lactate/choline, lactate/creatine, lactate/alanine and the combined lactate/(choline + creatine + alanine) ratios in LNCaP‐LN3 cells relative to LNCaP cells. No significant changes in metabolite ratios were found in LNCaP cells following DCA treatment. As expected, LDH zymography assays showed an absence of the LDH‐B subunit in LNCaP‐LN3 cells, whereas both LDH‐A and LDH‐B subunits were present in LNCaP cells. DCA was shown to significantly modify the metabolite ratios in highly metastatic LNCaP‐LN3 cells, but not in poorly metastatic LNCaP cells. This effect was probably related to the absence of the LDH‐B subunit in LNCaP‐LN3 cells, and could have a bearing on cancer treatment with DCA and related compounds. © 2014 The Authors. NMR in Biomedicine published by John Wiley & Sons, Ltd.